2021
DOI: 10.1177/20503245211034930
|View full text |Cite
|
Sign up to set email alerts
|

Medical cannabis and epilepsy in the UK – A qualitative analysis of the carers’ perspective: “We're asking for quality of life for our children”

Abstract: Despite the legalisation of cannabis based medicinal products (CBMPs) in the UK in November 2018, today there remains a scarcity of NHS prescriptions, and many patients continue to face unsustainable financial costs to acquire their medicines. Following on from our previous quantitative study highlighting the effectiveness of CBMPs to treat severe intractable childhood-onset epilepsy, for the present study, we used a narrative, open-ended approach to interview parents/carers of these patients. 11 families were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Many of the measures that improved are associated with improved quality of life, which may suggest some of the effect of MC treatment on pain intensity was indirect, as previously discussed ( 51 53 ). Studies have shown that quality of life in patients that suffer from a severe illness such as cancer plays an important role in treatment adherence and success ( 54 – 56 ).…”
Section: Discussionmentioning
confidence: 71%
“…Many of the measures that improved are associated with improved quality of life, which may suggest some of the effect of MC treatment on pain intensity was indirect, as previously discussed ( 51 53 ). Studies have shown that quality of life in patients that suffer from a severe illness such as cancer plays an important role in treatment adherence and success ( 54 – 56 ).…”
Section: Discussionmentioning
confidence: 71%
“…Some doctors may have the paternalistic attitude that patients should defer to medical experts rather than discover their own solutions. A recent qualitative study of parents and carers using medical cannabis to treat their child’s epilepsy supports this conclusion, showing the challenging relationship between the doctor (who often lacks specific expertise on medical cannabis) and the parent (who had to develop expertise to be able to treat their child’s condition) 21…”
Section: Stigma and Fearmentioning
confidence: 95%
“…Hulaihel et al [ 3 ] conducted interviews with a sample of 15 medical cannabis users in Israel who also felt social stigma as a result of taking medical cannabis which negatively impacted their sense and presentation of self. Schlag et al [ 4 ] conducted interviews with 11 families in the UK with children who had been prescribed medical cannabis for epilepsy. The findings from this specific cohort foregrounded frustrations regarding national policy and the regulation of medical cannabis, and challenges experienced due to the lack of knowledge and understanding of medical cannabis within the wider UK healthcare system.…”
Section: Introductionmentioning
confidence: 99%